Exploring the barriers to access feminine healthcare among marginalized women in Bangladesh and design implications - Puja, Sreya Sanyal; Neha, Nahian Noor; Alif, Ofia Rahman; Sultan, Tarannaum Jahan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.